Síntese e caracterização de poliuretano ramificado com potencial aplicação em engenharia de tecidos - Hoffmann, Mauricio da Silva (2016)
Polyurethanes (PU) are widely used as biomaterials because it has good compatibility, and desirable mechanical properties and branched polyurethanes have shown besides these characteristics, an appreciable stability to hydrolytic and enzymatic degradation. Within this context, this study aimed to synthesize branched polyurethanes from the addition of pentaerythritol and evaluate its potential use as scaffolds in tissue engineering. Polycaprolactone diol (PCL) as polyol and pentaerythritol (PETT) in different amounts (5, 10 and 15% w/w relative to the polyol) as well as the hexamethylene diisocyanate (HDI) were used in the synthesis of the branched PU. These branched PU (PU-PETT) were evaluated for structural, morphological, mechanical, thermal and solubility in various organic solvents and compared to the linear PU (without PETT). Among the branched PU, PU-PETT 5% showed better morphological and tensile strength characteristics, so it was used to prepare membranes leached with the linear PU. The leached membranes were evaluated for their structural, morphological, mechanical, thermal properties, wettability, hydrolytic degradation, calcification and swelling degree. The leached membrane PU-PETT 5% showed high porosity and interconnectivity, greater thermal stability compared to linear PU leached membrane, despite the lower degree of crystallinity and molar weight. Also, the PU-PETT 5% membrane exhibited the ability of calcium phosphate biomineralization, good wettability, higher stability hydrolytic degradation and greater swelling as compared to linear PU membrane. Thus, it can be concluded that the membrane PU-PETT 5% exhibited characteristics suitable for use as biomaterials in tissue engineering.